The impact of rootstock on peach tree vigor, light environment, fruit quality, and metabolism - Pieper, Jeffrey Ross, author; Minas, Ioannis, advisor; Bunning, Marisa, committee member; Caspari, Horst, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2024)
The key to Colorado's successful peach industry is superb fruit quality. The fruit quality growers achieve allows for the highest premium 'farm-gate' price per pound in the nation. Fruit quality is created in the orchard via the interaction of several pre-harvest factors. One critical pre-harvest factor that has several knock-on effects for orchard management decisions is rootstock selection. Rootstock selection has the potential to impact the longevity, productivity, efficiency, and profitability of an orchard, and is dependent on climatic and edaphic environments as well as the soil microbiome. Rootstock selection may also allow growers to augment orchard design through vigor manipulation. In Colorado, growers are faced with relatively short growing seasons, sudden fall and spring frost events, and calcareous soils which limit the availability of certain nutrients. The unique growing environments coupled with the need for high quality fruit production makes rootstock selection limited. Identifying rootstocks suitable for production in Colorado and determining how they impact fruit quality is paramount. While previous studies have evaluated rootstocks for their performance and relationship to fruit quality, few have limited confounding factors such as crop load, canopy position, and or physiological maturity when assessing fruit. The following experiments evaluated twenty-one genetically diverse rootstocks for their phenotypic and agronomic performance and potential use in Colorado production systems. The nine-year performance review, in chapter one, details the productivity and suitability of seventeen genetically diverse peach rootstocks in Colorado growing conditions. The trial determined rootstock vigor strongly correlates with cumulative yield. However, vigor also showed an inverse relationship with internal fruit quality development measured as dry matter content (DMC) and soluble solids concentration (SSC). The trial showed interspecific peach and non-peach hybrids outperformed peach seedling rootstocks. One interspecific peach rootstock in particular, 'Krymsk® 86', performed exceptionally well and has since been widely adopted by industry. By controlling for several confounding factors, the rootstock vigor trial, chapter two, demonstrated the true impact of vigor and light availability on fruit quality enhancement and primary metabolite profiles. Fruit developing in reduced vigor canopy of the dwarfing rootstock 'Krymsk® 1' had increased light availability and enhanced internal fruit quality parameters (DMC and SSC) at harvest. Mesocarp metabolites relating to internal quality showed they are up and down accumulated by rootstock vigor and the light environment. Several metabolite classes including soluble sugars, cyclitols, flavanols, and chlorogenic acids were associated with 'Krymsk® 1', a low vigor rootstock that had high light availability and enhanced fruit quality profiles. 'Atlas™' and 'Bright's Hybrid® 5', both vigorous rootstocks, showed low light availability and reduced fruit quality. The vigorous rootstocks also showed an increase of amino and fatty acids compared to the standard and dwarfing rootstocks. The six-year physiological and agronomic performance of modern semi-dwarfing rootstocks trial, chapter three, reiterated the impact of vigor on yield, light availability, and fruit quality development. Furthermore, the trial showed increased vigor was related to an increase of gummosis incidence and severity. Also, intra-specific Prunus hybrids had increased rates of proleptic shoot formation, however, some showed they were susceptible to iron chlorosis. Overall, the rootstock trials identify key parameters of performance and suitability in Colorado production systems. The outcomes indicate that rootstocks with increased vigor resulted in higher yields per tree, however, lower light availability in the canopy decreased DMC and SSC. While rootstock genotype and vigor are influencing peach fruit development and quality, their effect on light availability may play a more significant role in achieving optimal yield and fruit quality and augmented metabolite profiles. Additionally, this work demonstrates the importance of controlling for confounding variables when evaluating preharvest factors for their impact on internal fruit quality and metabolite profiles.
Keywords: equal maturity; internal fruit quality; semi-dwarfing; GC-MS; dry matter content; rootstock